Origins of mass customization: The individual consumer-brand interactions within mass markets in the marketing - Arbaiza Rodríguez, Francisco (2022)
This paper aims to point out the roots that have shaped the platform that sustains and justifies the existence of a new marketing formula focused in the individual consumer experience. As this consumer society has oriented its demands almost exclusively in image, based on motivational theories and lifestyle, marketing activity has followed a gradual change, exposed in the phenomenon of mass customization. The marketing machine, supported by new technologies, has let consumers desynchronize common activities, individual consumption and customized use of products and services. In summary, has arisen a massive and personal consumption at the same time.